Crosstalk in DAQ-based measurement platforms for structural health monitoring: effects on damage detection and mitigation methods - Rezende, Guilherme Marconato [UNESP]; Baptista, Fabricio Guimaraes [UNESP] (IOP Publishing, 2025)
Data acquisition (DAQ) devices have been widely used in measurement platforms for structural health monitoring. However, these devices exhibit internal crosstalk, which is interference between different channels. Such interference is not easily perceived and can affect the detection of incipient damage. This study has focused on the crosstalk effects on damage detection methods based on Lamb waves, acoustic emission and electromechanical impedance. Experiments were performed on two independent aluminum structures and measurements were collected using different DAQ devices to evaluate the crosstalk effects. Structural damage was quantified with root mean square deviation index and compared to the index change erroneously caused by crosstalk. Finally, two crosstalk mitigation methods, based on frequency response function and voltage follower with operational amplifier, were evaluated. Results show that crosstalk in DAQ devices can significantly impair the detection of minor damage, and the use of voltage followers is a simple and effective mitigation method.